Application of wastewater with high organic load for saline-sodic soil reclamation focusing on soil purification ability - M.A. Kameli; M. Chorom; N. Jaafarzadeh; H. Janadeleh (Global Journal of Environmental Science and Management)
Fresh water source scarcity in arid and semiarid area is limitation factor for saline-sodic soil reclamation. The reusing of agricultural drainage and industrial wastewater are preferred strategies for combating with this concern. The objective of current study was evaluation in application of industrial sugar manufacture wastewater due to high soluble organic compounds in saline-sodic and sodic soil. Also soil ability in wastewater organic compounds removal was second aim of present study. Saline-sodic and sodic soil sample was leached in soil column by diluted wastewater of amirkabir sugar manufacture in Khuzestan Province of Iran at constant water head. Sodium, electric conductivity and chemical oxygen demand of soil column leachate were measured per each pore volume. The experimental kinetics of wastewater organic compounds on two saline-sodic and sodic soil were also investigated by three pseudo second order, intra particle diffusion and elovich model. The results of current study showed that electric conductivity of saline-sodic soil was decreased to 90% during 3 initial pore volumes, from other side exchangeable sodium percent of saline-sodic and sodic soil decreased 30 and 71 percent, respectively. There were no significant different between wastewater chemical oxygen demand removal by saline-sodic and sodic soil in both batch and column studies. Wastewater chemical oxygen demand was decreased to 35% during pass through soil column. The results showed that the adsorption kinetics of wastewater organic compounds were best fitted by the pseudo-second order model with 99 percent correlation coefficient (r2=0.99%).